Algorithms and software for areal surface texture function parameters. (14th September 2017) - Smith, I M; Harris, P M; Todhunter, L D; Giusca, C; Jiang, X; Scott, P; Leach, R K
Abstract: Software for the evaluation of areal surface texture function parameters is described. Definitions of the parameters, expressed in terms of the inverse areal material ratio function, are provided along with details of the numerical algorithms employed in the software to implement calculations to evaluate approximations to the parameters according to those definitions. Results obtained using the software to process a number of data sets representing different surfaces are compared with those returned by proprietary software for surface texture measurement. Differences in the results, arising from different choices being made when implementing the steps in the parameter evaluation process, are discussed.